Assessment of Potentially Inappropriate Prescribed Medications in Older Patients Using STOPP/START Criteria at Soba University Hospital: A Descriptive Retrospective Study - Azza A. Mohammed; Kannan O. Ahmed; Bashir A. Yousef (Research Center for Rational Use of Drugs (RCRUD), 2022)
Background: Potentially inappropriate prescriptions (PIPs) have significant clinical, humanistic, and economic impacts. Identifying PIPs may reduce their burden of adverse drug events. "Screening Tool of Older Person's potentially inappropriate Prescriptions (STOPP) and Screening Tool of Alert doctors to the Right Treatment (START) criteria" are promising tools that formulated to identify potentially inappropriate medications (PIMs) and potential prescribing omissions (PPOs) in geriatrics. To determine the PIMs and PPOs using STOPP/START criteria and to determine the most frequent PIPs. Methods: The study was a descriptive cross-sectional hospital-based retrospective study. Medical files of elderly (≥65 years) patients admitted to the internal medicine unit at Soba university hospital from January to July 2020 were used. Data were collected using a checklist of STOPP/START criteria (version 2) to determine PIPs. Statistical package for social sciences was used for data analysis. Results: A total of 100 patients were included, around 59% were aged between 65-70 years, and 58% were males. The mean number of medications was 5.3 ± 1.9 drugs/patient. The results showed that the prevalence of PIPs was 68%. The STOPP criteria detected 209 PIMs in 42 patients, whereas the START criteria detected 155 PPOs in 45 patients. Furthermore, the drugs that used beyond the indication period was the most common PIMs, whereas the most detected PPOs were observed in the cardiovascular system medications. Conclusion: The study revealed a high prevalence of PIPs among elderly patients. This necessitates a further evaluation of its impact on clinical outcomes and implements interventions to improve prescribing practice.